Collaborative Practice: Empowered by Inner Work - Lois E. Wilkins RN, MSN, ARNP, CNS (SAGE Publishing, 1995)
If alternative practitioners hope to work in collaboration with more traditional providers, inner work is necessary. Alternative practitioners must begin to understand their own perspective, emotional triggers, weaknesses, and strengths. The Grimm Brothers' fairy tale, The Handless Maiden's Tale , is used to dramatize the process of inner work.